Identification of micronutrient-rich germplasms of barley for mid-hills and Terai region of Nepal - Pokharel, Bhanu Bhakta; Adhikari, Parbati; Thapa, Shailendra; Sharma, Shashi Ram (Journal of Agriculture and Natural Resources, 2022)
Zinc and iron deficiencies, common in many parts of the world, having risk factors that raise the burden of disease with high child and adult mortality. Breeding efforts for exploring barley grains with higher zinc and iron are underway. A study was conducted during the normal barley growing season of 2017 to identify the barley genotypes with higher concentration of protein, starch, iron and zinc for the mid-hill and Terai conditions of Nepal. An augmented block design was followed, and two improved varieties i.e., Bonus and Solu Uwa were used as repeated checks. The average grain protein, starch, zinc, and iron content were 11.9%, 55.6%, 47.4 mg/kg and 41.4 mg/kg at Dailekh and 11.3%, 53.3%, 46.6 mg/kg and 39.9 mg/kg at Rampur, respectively. The grain protein content was found up to 19.8% (AM-55, AM-45, AM-88 at Dailekh) and 16.6% (AM-81, AM-77, AM-98 at Rampur). Similarly, the highest grain zinc content was found 97 mg/kg (AM-6, AM-138 and AM-125 at Dailekh) and 92 mg/kg (AM-226, AM-99 and AM-227 mg/kg at Rampur). The highest iron content 71 mg/kg ( AM-2, AM-43, AM-4 at Dailekh) and 63 mg/kg (AM-90, AM-168 and AM-92 at Rampur). The identified genotypes with higher grain elements concentration are valuable resources for Nepal's barley breeding program that helps develop quality and nutritious barley varieties.